QBasic - Bent, Robert J. (PWS, 1995)
Introduction to computer programming. The QBasic environment. Programming in QBasic. A first look at loops. More on the Print statement. More on input/output programming. Modular programming: Qbasic procedures. QBasic selection structures. Counter-controlled loops: the FOR and NEXT statements. Arrays. Functions.